Metode Komunikasi Dakwah Majelis Ulama Indonesia (MUI) Dalam Mengatasi Paham Radikal Di Kabupaten Labuhanbatu - Muhammad Ferry Syahputra; Muktarruddin Muktarruddin; Elfi Yantii Ritonga (Fakultas Dakwah dan Komunikasi UIN Sumatera Utara Medan, 2021)
This research is motivated by the rise of radicalism ideology lately, especially in one of the organizations in the city of Rantau Prapat. The purpose of this study was to find out the dangers of radical understanding conveyed by Muhamamd Gaddafi and members of the Islamic Generation Study Circle (LSGI) to the Labuhanbatu Rantauprapat community and the application of MUI da'wah communication methods in overcoming radical LSGI understanding in Labuhanbatu, and how the Indonesian Ulema Council in overcoming obstacles. - Barriers to the communication of the da'wah. This research uses qualitative research. Data were collected by interview, observation, documentation and literature review. This research was analyzed inductively. The results obtained show that the Labuhanbatu MUI has succeeded in reducing the expansion of radical understanding brought by Muhammad Gaddafi and members of the LSGI in Labuhanbatu Rantauprapat, by applying the da'wah communication method, with this success it is expected to there will be no more people who are tempted by this radical understanding. MUI itself has provided guidance to Muhammad Gaddafi and members of the LSGI by applying the da'wah communication method, the public is no longer restless and afraid of the spread of this understanding, because they are no longer radical